Korelasi Jumlah Netrofil, Limfosit, dan Monosit dengan Kadar Albumin Urin pada Pasien DM Tipe 2 dengan Mikroalbuminuria - Edy Purwanto (Universitas Muhamadiyah Surakarta, 2009)
The most common complication of diabetes is diabetic nephropathy which is a progressive disease and in the terminal stages, needs a very large cost of care. Nephropathy diabetic can be prevented if it is detected earlier. Microalbuminuria is a test to detect nepropathy diabetic early nowadays, but it is still considered expensive by the majority of the community and has not been widely done in laboratories. What ever it needs other alternatives, such as neutrophils, lymphocyte, and monocyte counts. The purpose of this study is to analyse the correlations between neutrophils, lymphocyte, monocyte counts and urine albumin levels in type2 diabetes with microalbuminuria. The research design is analytic observational with cross sectional approach. Twenty two patients met the inclusion criteria. Their urine albumin levels tested by Nycocard® U-ALBUMIN reagent. Neutrophils, lymphocyte, monocyte count was examined by hematology analyzer CELL-Dyn 3700. The correlations between neutrophils, lymphocyte, monocyte counts and urine albumin levels analyzed using coefficient correlation Spearman's. No correlation between neutrophil countsand urine albumin levels (r= -0,250;p=0,263). No correlation between monocyte counts and urine albumin levels (r= -0,191;p=0,395). No correlation between lymphocyte counts and urine albumin levels (r=0,130;p=0,565) in type 2 diabetes with microalbuminuria. No correlation between neutrophils, lymphocyte, monocyte counts and urine albumin level in type 2 diabetes patients with microalbuminuriaKeywords: type 2 diabetes, neutrophils, lymphocytes, monocytes, microalbuminuria.